Dense mullite zirconia composites obtained from the reaction sintering of milled stoichiometric alumina zircon mixtures by SPS - Rendtorff Birrer, Nicolás Maximiliano (2014)
The main objective of this article is to obtain dense (porosity under 0.5%) polyphasic ceramics belonging to the Al2O3–SiO2–ZrO2 system by SPS sintering of high energy powders milled drily; the stoichiometric (54.45:45.54 zircon–alumina, weight basis) mixture was explored in this work. Particularly the principal sintering variables: sintering temperature and dwell time were investigated. The textural, structural and microstructural changes were evaluated together with the hardness and toughness of the obtained ceramics and their microstructure. The effect of the mechanical pre-treatment was carried out by X-ray diffraction and particle distribution evaluation. Due to the rapid heating process an incomplete reaction was achieved in several cases, as a consequence multiphasic ceramics with different alumina, mullite, zircon and zirconia contents were obtained. The mechanical pretreatment used resulted in a homogeneous dry mixture with a partial (≈20%) zircon dissociation, apparently enhanced by the alumina presence. This together with the posterior SPS processing permitted to obtain fully dense ceramic composites at a very low temperature (1300 °C) without the requirement of any additive. The reactions from alumina zircon mixtures to mullite zirconia occur 200 °C below conventional processing routes and at least 50 °C below the reported SPS based materials processed from un-milled mixtures. The microstructure and mechanical properties obtained were comparable to the ones obtained by other processing routes. Finally some interesting group correlations were found for the developed materials while the hardness is directly correlated with the density and the fracture toughness is correlated with the zirconia (m+t) content.